Banished to the great northern wilderness : political exile and re-education in Mao's China - Wang, Ning, 1964- (Cornell University Press, 2017)
"This book illuminates the dark corners of life in Mao's China, forty years after the Paramount Leader's death. During the Anti-Rightist Campaign of 1957-58, scholars, artists, journalists, and others whom the state considered suspicious "intellectuals" were targeted for "re-education." In Banished to the Great Northern Wilderness, Ning Wang draws on labour camp archives, memoirs, and interviews to provide a remarkable look at the suffering and complex psychological world of banished Chinese intellectuals. His use of these newly uncovered Chinese-language sources paints a vivid and nuanced picture that challenges our concept of the intellectual as renegade martyr."-- Provided by publisher.
Keywords: Zhongguo gong chan dang -- History -- 20th century.; Zhongguo gong chan dang; Forced labor -- China -- Manchuria -- History -- 20th century.; Labor camps -- China -- Manchuria -- History -- 20th century.; Political persecution -- China -- Beijing -- History -- 20th century.; Intellectuals -- China -- Beijing -- History -- 20th century.; Exiles -- China -- Manchuria -- History -- 20th century.; Manchuria (China) -- History -- 20th century.; China -- History -- 1949-1976.; Travail forcé -- Chine -- Mandchourie -- Histoire -- 20e siècle.; Abris pour travailleurs -- Chine -- Mandchourie -- Histoire -- 20e siècle.; Répression politique -- Chine -- Pékin -- Histoire -- 20e siècle.; Intellectuels -- Chine -- Pékin -- Histoire -- 20e siècle.; Mandchourie (Chine) -- Histoire -- 20e siècle.; Chine -- Histoire -- 1949-1976.; SOCIAL SCIENCE -- Penology.; Exiles; Forced labor; Intellectuals; Labor camps; Political persecution; China; China -- Beijing; China -- Manchuria; 1900-1999; History